The Lived Experiences of Adult Crystal Methamphetamine Users: A Qualitative Study - Girija Dadhe; Cathy Bettman (Psychotherapy and Counselling Journal of Australia)
Crystal methamphetamine, also known as "ice" or "crystal meth," is a potent psychostimulant drug that can cause irreversible physical and psychological damage to users (Halkitis, 2009). This qualitative research investigated the lived experiences of users, the background of their addiction, and the effects of using this drug. Six men between 31 and 39 years of age participated in the research. Three main themes emerged from the data: context, aftermath, and recovery. Respondents identified an inability to cope with dysfunctional family environments and negative social influences as the main causes of their crystal methamphetamine addiction, which resulted in significant adverse effects on their physical and mental health, relationships, occupation, and behaviour. They expressed a need for integrated and family focussed services, as well as a decriminalised approach towards crystal methamphetamine usage to help individuals and their families in the recovery journey.